Những yếu tố tác động đến động lực làm việc của giảng viên ở các trường đại học trong giai đoạn hiện nay: một số vấn đề lí luận - Nguyễn , Thị Thi (Tạp chí Giáo dục, 2022)
In universities, the teaching staff is an important factor that determines teaching quality. If lecturers are motivated to work, the work efficiency will be promoted, and at the same time, they will constantly improve and develop themselves. This study has identified a number of internal and external factors affecting working motivation of lecturers at universities in the current period; thereby proposing some recommendations to help schools with motivating teachers such as: building a appropriate system of rules and regulations on regimes and policies, salary payment and appropriate reward work; developing a democratic and friendly working environment; establishing fair and objective criteria for lecturers evaluation, etc. Investigation into lecturers’ working motivation is a premise to ensure consistency in managing and stabilizing personnel in universities.